Changes in multiple environmental factors additively enhance the dominance of an exotic plant with a novel trade‐off pattern. (3rd April 2020) - Qiu, Shiyun; Liu, Shuangshuang; Wei, Shujuan; Cui, Xinhong; Nie, Ming; Huang, Jingxin; He, Qiang; Ju, Rui‐Ting; Li, Bo
Abstract: Whether global changes impact native and exotic species differently is unclear, because the changes may favour both native and exotic species over competitors. Previous studies have mainly focused on the separate effects of different environmental changes, but plant communities are influenced by the changes in multiple environmental factors, and it is still unclear whether native and exotic species respond similar to the combined effects of these factors. We hypothesized that differences in interspecific trade‐offs between native and exotic species can lead to the dominance of exotic species when the species are simultaneously subjected to multiple environmental changes. Using coastal saltmarsh plant communities as the study system, we experimentally manipulated flooding and nutrient enrichment, examined the interspecific trade‐offs between competitiveness and stress tolerance for two native and one exotic species, and explored the combined effect of the two environmental changes on both native–native and native–exotic species interactions. We found that flooding and nutrient enrichment oppositely affected native–native species interactions but additively affected native–exotic species interactions. The two factors together resulted in no net change in the relative advantages between the two native species but enhanced the dominance of the exotic species over the native species. This disparity occurred because the exotic species was not subject to the interspecific trade‐off between competitiveness and stress tolerance that constrained the native species. Synthesis. Our results suggest that changes in multiple environmental factors favour exotic species because of evolutionary novel trade‐off patterns. Mechanisms underlying species coexistence in the invaded community such as interspecific trade‐offs need to be considered when future attempts are made to predict the effects of global changes on biological invasions. Abstract : Multiple environmental changes together resulted in no net change in the relative advantages between the native species but enhanced the dominance of the exotic species with a novel trade‐off pattern. The results suggest that changes in multiple environmental factors favour exotic species because of the evolutionary novel trade‐off pattern. Mechanisms underlying species coexistence in the invaded community such as interspecific trade‐offs need to be considered when further attempts are made to predict the effects of global changes on biological invasions. 摘要: 全球变化对外来物种和土著物种的影响是否一致的问题一直备受争议，因为外来物种和土著物种的竞争优势都可能因环境变化而改变。以往的研究主要关注单个环境因素变化的影响，但自然界中植物群落往往同时受到多个环境因素变化的影响，这些因素的共同作用对外来物种和土著物种的影响是否存在差异，这一问题仍不明确。 本研究假设，外来物种和土著物种在种间权衡上存在差异，这种差异将导致多重环境因素变化背景下外来物种在群落中占据更高的优势度。 为了验证这一假设，本研究以盐沼植物群落为对象，设计了水位胁迫和营养输入实验，检验了外来物种和土著物种在竞争能力和耐胁迫能力间的权衡模式，并分析了上述两种环境因素变化对土著物种-土著物种和土著物种-外来物种种间相互作用的影响。 结果发现，水淹胁迫和营养输入在影响不同土著物种种间关系上的效应相互抵消，而在影响土著物种与外来物种种间关系上不存在效应相互抵消的现象。两种环境因素变化的共同作用，未改变不同土著物种在种间的相对优势，但增加了外来物种相对于土著物种的种间优势度。这种差异产生的原因是，不同的土著物种在竞争能力和耐胁迫能力上存在种间权衡，而外来物种未受到这种权衡的约束。 上述结果表明，多重环境因素变化有利于与土著物种权衡模式不同的外来物种的入侵。因此，未来有关全球变化对生物入侵影响的研究，需关注群落内的种间权衡等物种共存驱动机制的作用。